Potential risk of automation for employment in Slovakia: A district- and industry-level analysis - Erika Majzlíková; Matej Vitáloš (University of Economics in Bratislava, Department of Economic Policy, 2021)
The aim of this paper is to examine the potential impacts of automation and digitalisation on the Slovak labour market, which, according to several studies, belongs to a group of countries with the highest risk. To quantify the share of employment at a high risk of automation, we use detailed employment data and automatability estimates (or substitutional potentials) for individual occupations according to three different methodologies: by Frey and Osborne (2013), Dengler and Matthes (2018), and Mihaylov and Tijdens (2019). In 2019, depending on the approach taken, the share of employment in Slovakia at a high risk of automation ranged from about 20 to 47%. Districts at the highest risk of automation include Kysucké Nové Mesto, Bytéca, Myjava, Skalica and Krupina, while districts with the lowest share of employment at risk are Svidník, Levoéca, Ruézomberok, Koésice I and Trebiésov. A key point is that technological progress is not likely to increase the existing regional differences in Slovakia or have a greater impact on districts with high unemployment. Other findings show that employees with a lower income face a higher risk of losing their job as a result of technological progress. Industries with the largest share of employment at a very high risk include many manufacturing industries, as well as wholesale and retail trade. In terms of occupations, mechanical machinery assemblers and electrical equipment assemblers face the highest risk. Regarding trade, occupations potentially facing a high risk include shop sales assistants, cashiers, ticket clerks, commercial sales representatives, and stock clerks.
Keywords: J21; J23; O33; 330; Automation; digitalisation; employment; occupations; regions; Slovakia